Pengaruh Harga dan Promosi via Sosial Media Terhadap Keputusan Pembelian Produk Kuliner Secara Online di Masa Pandemi Covid-19 (Studi pada Pelajar di DIY, Indonesia) - Virginita Rianasari (International Journal Administration, Business & Organization, 2022)
Business solutions in the midest of the Pandemic Covid-19 discussed the impact of the pandemic on the community's economy, especially in Yogyakarta. Not less than people who have been affected by Covid-19 have swerved to find another fortune by selling whatever they could, and this research focuses on the culinary business by online marketing. The purpose of this study was to determine the partial and simultaneous effect of price and promotion via social media on online purchasing decisions for culinary products during the Pandemic Covid-19. This study explains the effect of price and promotion on consumer decision making in buying culinary products online during the Pandemic Covid-19. The targeted online culinary market was young students in the Special Region of Yogyakarta (DIY). The results showed that either partially or simultaneously, prices and promotions through social media had a positive and significant effect on online purchasing decisions for culinary products. KEY WORDS: Online Business, Culinary Business, Pandemic Covid-19, prices, promotions and purchasing decisions